Short-Term Effects of Intra-Articular Hyaluronic Acid Administration in Patients with Temporomandibular Joint Disorders - Sikora, Maciej (J Clin Med, 2020)
The study described in this paper was conducted to assess the short-term outcomes of intra-articular administration of hyaluronic acid in patients with symptoms of temporomandibular joint disorders. A group of 40 patients suffering from temporomandibular joint disorders underwent a series of hyaluronic acid intra-articular injections. Questionnaires and clinical examinations were conducted to assess stress exposure of the subjects and to evaluate short-term treatment outcomes, i.e., reducing joint and muscle pain and increasing the mobility of the mandible. A weak positive correlation between stress exposure and pain was observed. As a result of treatment, 61% of subjects revealed a total reduction of muscle pain, while joint pain completely resolved in 88% of patients. Mandibular mobility increased by 11%, 31%, 9%, and 11% regarding opening, protrusive, and lateral right and left movements, respectively. The study confirms the short-term effectiveness of intra-articular administration of hyaluronic acid on reducing joint and muscle pain in patients with articular disc displacement. The treatment positively affected the mobility of the mandible in all directions. The verification of late treatment effects of hyaluronic acid viscosupplementation requires the continuation of the research.